BUILDING ONLINE LEARNING COMMUNITY IN SYNCHRONOUS AND ASYNCHRONOUS LEARNING MODELS - M. Ali Ghufron; Arditya Prayogi; Fitri Nurdianingsih (IKIP Siliwangi, 2023)
This study aimed to describe the teachers' efforts in building online learning community (OLC) in synchronous and asynchronous learning models. This study employed a qualitative case study involving four teachers from 2 universities in Central Java and East Java, Indonesia. The data of this study were garnered through in-depth interviews and, then, were analyzed narratively. The findings revealed that OLC was reflected in three elements, i.e., cognitive presence, social presence, and teaching presence (Cleveland-Innes et al., 2018). To build OLC in both synchronous and asynchronous learning models, the teachers employed several strategies, e.g., doing an exploration phase through information exchanges, connecting ideas, and applying new ideas (cognitive presence), opening two-way communication and encouraging collaboration (social presence), explaining instructional materials and focusing discussion, and doing reflection and checking for students' understanding (teaching presence). The difference between OLC in synchronous and asynchronous learning models lies in the teaching mode. In the synchronous learning model, the OLC was built through video conferences, such as Zoom meetings or Google Meet. Meanwhile, the asynchronous learning model built the OLC through Moodle or Google Classroom and/or WhatsApp and Telegram discussion. This study concludes that teachers' pedagogical competence is pivotal in building OLC in synchronous and asynchronous learning models.